Advances in 4D Printing: Materials and Applications. (26th November 2018) - Kuang, Xiao; Roach, Devin J.; Wu, Jiangtao; Hamel, Craig M.; Ding, Zhen; Wang, Tiejun; Dunn, Martin L.; Qi, Hang Jerry
Abstract: 4D printing has attracted tremendous interest since its first conceptualization in 2013. 4D printing derived from the fast growth and interdisciplinary research of smart materials, 3D printer, and design. Compared with the static objects created by 3D printing, 4D printing allows a 3D printed structure to change its configuration or function with time in response to external stimuli such as temperature, light, water, etc., which makes 3D printing alive. Herein, the material systems used in 4D printing are reviewed, with emphasis on mechanisms and potential applications. After a brief overview of the definition, history, and basic elements of 4D printing, the state‐of‐the‐art advances in 4D printing for shape‐shifting materials are reviewed in detail. Both single material and multiple materials using different mechanisms for shape changing are summarized. In addition, 4D printing of multifunctional materials, such as 4D bioprinting, is briefly introduced. Finally, the trend of 4D printing and the perspectives for this exciting new field are highlighted. Abstract : 4D printing allows 3D printed structures to change their configurations or functions with time in response to external stimuli. Herein, the material system is reviewed based on the mechanism and potential applications for advances in 4D printing. The trends of 4D printing are discussed and the perspectives for this exciting new field are provided.